The Influence of Using Emancipated Curriculum-Based Biology Teaching Modules on Students' Biology Learning Outcomes - Rizalia, Syarif; Dwihapsari, Nita (KULIDAWA, 2024)
This study aims to 1) interpret the use of a biology teaching module based on the Emancipated Curriculum and 2) interpret the significance of using the biology teaching module on the biology learning outcomes of grade X students at SMA Negeri 11 Kendari. This type of research is quantitative research. The object of the study was grade X students of SMA Negeri 11 Kendari who used Emancipated Curriculum-based biology teaching modules. The learning material chosen for the research was biodiversity. Data collection techniques were questionnaires, interviews, and documentation, which were analyzed using descriptive and inferential statistical analysis. The results of the study show that: 1) the use of a biology teaching module based on the Emancipated Curriculum at SMA Negeri 11 Kendari is in the moderate category, reaching a percentage of 63.00%, so it can be interpreted that the use of the biology teaching module in class has been quite well achieved and the feedback indicator received the highest percentage, reaching 74.25%, falling into a high category; 2) there was an influence of competence of using an  Emancipated Curriculum-based biology teaching module on students' learning outcomes at SMA Negeri 11 Kendari with a significance value of (0.00) <α (0.05); 3) the use of biology teaching module on students' learning outcomes in grade X contributed 0.92, which means that the use of the biology teaching module influenced the success of students' biology learning outcomes by 92.50%.